Immunohistochemical expression of HLA-DR in the conjunctiva of patients under topical prostaglandin analogs treatment - Rodrigues, Maria de Lourdes Veronese; Felipe Crosta, Daniela Pereira Da Silva; Soares, Christiane Pienna [UNESP]; Deghaide, Neifi Hassam Saloum; Duarte, Roberta [UNESP]; Sakamoto, Fabiano S.; Furtado, João Marcello Fortes; Paula, Jayter Silva; Donadi, Eduardo Antonio; Soares, Edson Garcia (Wolters Kluwer, 2009)
PURPOSE: Subclinical inflammation may be observed in patients using topical antiglaucomatous drugs. The objective of this study was to investigate inflammation in conjunctiva of glaucoma patients using prostaglandin analogs, by the detection of an immunogenetic marker (HLA-DR) and compare the effect of 3 different drugs: latanoprost, bimatoprost, and travoprost in the induction of this inflammation. SUBJECTS AND METHODS: Thirty-three patients with primary open-angle glaucoma were evaluated without and with prostaglandin analogs topical therapy. Imprints of conjunctival cells were obtained, fixed on glass slides, and prepared for immunohistochemical analysis. RESULTS: Before the use of prostaglandin analogs, 4 of the 33 patients evaluated presented expression of HLA-DR in the conjunctiva (mild). After 1 month on prostaglandin analog treatment, all but 1 patient presented HLA-DR staining. HLA-DR expression of these 32 patients was scored as mild (19 patients), medium (11 patients), or intense (2 patients). The differences were statistically significant both when the presence and the increased expression of HLA-DR were considered (P<0.001). When the 3 different groups were analyzed (latanoprost, bimatoprost, and travoprost) no statistically significant difference was found (P=0.27). CONCLUSIONS: The use of prostaglandin analogs eye drops provokes a subclinical inflammatory reaction, observed by HLA-DR expression, even after a short period of treatment, independently of the class of the prostaglandin analogs used. © 2009 Lippincott Williams & Wilkins, Inc.
Keywords: Conjunctival in.ammation; Glaucoma treatment; HLA-DR; Prostaglandin analog; bimatoprost; HLA DR antigen; latanoprost; travoprost; amide; antihypertensive agent; biological marker; cloprostenol; drug derivative; prostaglandin F; adult; aged; antigen expression; clinical article; conjunctiva; conjunctivitis; controlled study; drug effect; female; human; human cell; immunohistochemistry; male; open angle glaucoma; priority journal; chemically induced disorder; enzyme immunoassay; metabolism; middle aged; topical drug administration; Administration, Topical; Aged; Aged, 80 and over; Amides; Antihypertensive Agents; Biological Markers; Cloprostenol; Conjunctivitis; Female; Glaucoma, Open-Angle; HLA-DR Antigens; Humans; Immunoenzyme Techniques; Male; Middle Aged; Prostaglandins F, Synthetic